Economic growth in Peru: A model of projection and evaluation of its determinants - García Sandoval, Carlos (2015)
It is known that over long periods GDP growth, even at small annual rates, could have a significant effect on the standard of living of a population. For example, a GDP growth rate in the order of 2.5% per year would lead to a doubling of GDP in about 30 years, while a growth rate of 8% per year (as has been observed in certain Asian countries) would lead to the same doubling but over a period of only 10 years. Unfortunately, these measures are only relative because, when the population increases, improvements in the standard of living would only be possible if GDP grows faster than the population itself. This helps to understand why there are such different rates of economic growth in many regions of the world.